POLA KONSUMSI JAJANAN DAN KEJADIAN OBESITAS REMAJA DI SMP NEGERI 3 SUKAWATI - Made Dwi_Riski Wulansari; Hertog Nursanyoto; Putu Suiraoka (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Obesity is one of the nutritional problems that is still commonly found in Indonesia. Eating habit is one the factor of over nutrition or obesity in adolescents, especially from the pattern of snacks consumption.This study aims to find a description of patterns of snacks consumption and the proportion of adolescent obesity in SMP Negeri 3 Sukawati. The type of research used is Observational and cross sectional study design with 83 samples consisting of classes VII E and VIII C at SMP Negeri 3 Sukawati. The data collected is processed according to each category and presented in the form of distribution tables and cross tables. The results of this study found 21 samples (25.3%) with nutritional status overweight/obesity and 62 samples (74.7%) with normal nutritional status. And based on the type of snacks obtained that the highest distribution of 4 types of snacks (39.7%). It is recommended that the school canteen sell food that more variated and according to health requirements and good nutritional content such as the provision of snacks that are sold should pay attention to the expiration date and have a marketing authorization.Keywords: Patterns of snacks consumption., obesity, adolescents